Case Report: Surgical Treatment of Severe Facial Wounds and Proptosis in a Dog Due to a Traffic Accident - Kim, Jury; Kim, Daesik; Kim, Janghwan; Seo, Daeyun; Hwang, Hyejin; Kim, Yuna; Chung, Taekyu; Lim, Seongsoo; Lee, Hansol; Kim, Min Su (Frontiers in Veterinary Science, 2020)
Although facial wounds caused by traffic accidents in dogs are common, the surgical management of severe facial injuries involving the soft tissue, bone, dentition, nose and orbit are challenging. A 2-year-old Korean Jindo dog was diagnosed with severe skin defects of the face and proptosis caused by a vehicular accident. Along the left lateral maxilla, severe injury involving the overlying skin and platysma muscle occurred, to the extent that the middle part of the sphincter colli profundus pars intermedia muscle was exposed. Repair surgeries of the skin defects and globe displacement were performed using a local subdermal plexus rotation flap and a partial transposition of the dorsal rectus muscle combined with small intestinal submucosa (SIS) instead of enucleation as the first attempt. SIS was used to sustain the torn medial region. In this case, the surgery resulted in good cosmetic and functional outcome in the dog, despite the atypical complexities upon presentation.